EUCHEUMA COTTONI SEAWEED AGRIBUSINESS DEVELOPMENT STRATEGY IN EAST LOMBOK REGENCY - Widiyanti, Ni Made Nike Zeamita; Yusuf, M; Husni, Syarif; Sari, Ni Made Wirastika; Suparyana, Pande Komang (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2023)
Seaweed has many benefits for the food and non-food industries. This commodity is worth developing to increase farmers' income, but until now the seaweed agribusiness still has many obstacles. The purpose of this study was to analyze alternative strategies for developing seaweed agribusiness in Jerowaru District, East Lombok Regency. Respondents in this study were Eucheuma Cottoni seaweed farmers, academics, extension workers/chairmen of Gapoktan, and the Department of Maritime Affairs and Fisheries of East Lombok Regency. Data analysis using SWOT analysis. Based on the results of the analysis there are several alternative strategies for developing seaweed agribusiness in Jerowaru District, East Lombok Regency, namely: SO strategies; (1) The availability of potential land that is still widely available can be utilized to increase seaweed production, (2) Development of post-harvest activities, and (3) Developing post-harvest training activities, WO strategies; (1) Creating access between farmers and capital institutions with government assistance, (2) Increasing the role of government and extension workers to provide market information, and (3) Seaweed price policies to protect farmers, ST strategies; (1) Developing environmentally friendly seaweed cultivation for example with pipes, (2) Improving infrastructure, and (3) Creating healthy cooperation between middlemen and farmers, WT strategies; (1) Running farm management to be efficient and effective and (2) Creating healthy cooperation between middlemen and farmers.